WONDERLAND INDONESIA AS A BRAND IMAGE OF INDONESIA AS A CULTURED COUNTRY ON YOUTUBE CHANNEL - Kusumohendrarto, Raden Hadapiningrani; Fitri, Nofria Doni (Universitas Islam Nahdlatul Ulama Jepara, 2023)
The uniqueness of a country is a marker as well as a differentiator between one country and another. Indonesia itself is a country with expansive natural beauty, friendly local community wisdom, and a variety of cultures. The development of technology that facilitates human work and the existence of fast internet access today makes the exchange of information easy. The ease of information exchange currently has an impact on the entry of cultures from various countries to users in Indonesia, where local culture slowly begins to fade and unknown. The culture that owned by the Indonesian people is not attractive to young people because it is considered old-fashioned, less attractive, and there is no packaging that is more appropriate for the younger generation. This research was conducted using random observation and questionnaire methods to find out how much the younger generation loves the culture of the Indonesian people. While the research results are expected to be a lighter for Indonesian cultural creators.